The Effect Of Digital Marketing, Personal Branding, And Product Quality On Increasing Msmes Sales In Sukoharjo Regency - Sugiyanto, Aris Sander; Wahyudi, Tri Nur (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine the effect of digital marketing, personal branding, and product quality on increasing sales of micro, small, and medium enterprises (MSMEs) in the food and beverage sector in Sukoharjo Regency. The method used in carrying out research activities is a quantitative research method with an associative research type. Data were obtained through distributing questionnaires to 102 MSME respondents using multiple linear regression techniques with the SPSS application. The data show that the X1 variables of digital marketing, X2 personal branding, and X3 product quality have significant and positive values ​​​​on increasing MSME sales in the food and beverage sector in Sukoharjo Regency.